Analisis Kecelakaan Lalu Lintas (Accident Rate) Ruas Tol Pondok Aren – Serpong Tahun 2017 - 2021 - Rufaidah, Afifah Nur; Nu’man, Dimas; Ginting, Rasman (Institut Transportasi dan Logistik Trisakti, 2025)
The high movement of land transport mobility caused increase traffic accidents which becomes main problem of safety transportation system, without exception toll roads. Minimally obstacles when crossing toll roads make alternative commuter workers in mobilizing due to ease of access and time efficiency. Several factors caused accident such human, vehicle, and environment. The purpose the study was to determine the level of traffic accidents Toll Pondok Aren - Serpong, and to determine the blacklink segment using the accident rate method, then focus determining blackspot using the cumulative summary method, then do spot speed survey, questionnaire survey and interviews to analyze the behavior patterns Toll Pondok Aren - Serpong drivers and road inventory by evaluating existing conditions and road safety facilities blackspot locations. According the analysis, the accident prone location or blacklink Jakarta direction located at KM 10 + 600 - 9 + 800 with the accident rate is 52.29 accidents/100 JPKP and KM 8 + 600 - 6 + 400 is 31.03 accidents/100 JPKP with the blackspot STA 10 + 600 - 10 + 399 and STA 7 + 600 - 7 + 399 while Serpong route at KM 10 + 600 - 12 + 700 with the highest accident rate of 94.95 accidents/100 JPKP with blackspots STA 10 + 600 - 10 + 399 and STA 12 + 100 - 12 + 399.